Parameters derived from the postoperative decline in ultrasensitive PSA improve the prediction of radical prostatectomy outcome - Vesely, Stepan; Jarolim, Ladislav; Schmidt, Marek; Minarik, Ivo; Dusek, Pavel; Babjuk, Marko (World journal of urology, 2013)
PURPOSE: Contemporary tools estimating increased risk of prostate cancer (PCa) relapse after radical prostatectomy (RP) are far from perfect and there has been an intensive search for additional predictive variables. We aimed to explore whether the parameters of postoperative ultrasensitive prostate-specific antigen (PSA) decline provide additional information for predicting PCa progression. METHODS: A total of 319 consecutive men, with at least 2 years of follow-up after RP for clinically localized PCa were subjected to this study. Intensive postoperative measurements of ultrasensitive PSA resulted in total of 4028 PSA values available for statistical evaluation. Biochemical recurrence (BCR) was defined as PSA ≥0.2 ng/ml. The accuracy of predictive models was quantified with the area under the curve. RESULTS: Over a median follow-up of 43 months (24-99 months), 107 patients (34%) experienced BCR after RP. In patients with BCR, significantly higher values of PSA nadir (p < 0.001) and a decreased time interval from surgery to reach PSA nadir (p < 0.001) were observed. A multivariable Cox regression model confirmed that PSA nadir >0.01 ng/ml (HR 6.01, 95% CI: 3.89-9.52) and time to PSA nadir <3 months (HR 2.86, 95% CI: 1.74-5.01) were independent predictors of BCR. The inclusion of PSA nadir and the time to PSA nadir into the model resulted in improvement of predictive accuracy by 16% over the model designed on the basis of established parameters. CONCLUSIONS: Our results demonstrate that the level of PSA nadir and the time to PSA nadir determined by ultrasensitive assay significantly improve the identification of patients who are at high risk of disease recurrence after RP.
Keywords: senioři; proporcionální rizikové modely; Proportional Hazards Models; prostatektomie; senioři nad 80 let; Retrospective Studies; Prognosis; Cohort Studies; Middle Aged; ROC Curve; mužské pohlaví; nádory prostaty; Kallikreins; Neoplasm Recurrence, Local; Adult; prostatický specifický antigen; lokální recidiva nádoru; recidiva; ROC křivka; kohortové studie; Biomarkers, Tumor; Prostate-Specific Antigen; Aged, 80 and over; kalikreiny; prognóza; nádorové biomarkery; Prostatic Neoplasms; retrospektivní studie; Humans; Recurrence; Prostatectomy; lidé středního věku; dospělí; Aged; lidé; Male